If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(4n-2)=-2(7+7n)
We move all terms to the left:
-3(4n-2)-(-2(7+7n))=0
We add all the numbers together, and all the variables
-3(4n-2)-(-2(7n+7))=0
We multiply parentheses
-12n-(-2(7n+7))+6=0
We calculate terms in parentheses: -(-2(7n+7)), so:We get rid of parentheses
-2(7n+7)
We multiply parentheses
-14n-14
Back to the equation:
-(-14n-14)
-12n+14n+14+6=0
We add all the numbers together, and all the variables
2n+20=0
We move all terms containing n to the left, all other terms to the right
2n=-20
n=-20/2
n=-10
| 17×z=340 | | 18d+4=19d | | H(t)=-4.9t+8t+1 | | 8a^2-7=0 | | x-3x=123 | | 2x+.3=5x+1.3 | | X^2-6y-7=0 | | 215-v=128 | | 17-12y=-11y+4 | | 2(7v-4)+2(v-7)=-6v-3v | | 2,3x=-1 | | 13x-80=89 | | 10r-6=9r | | -1/6x=1 | | 9+b=-9-b | | 9x+12x+12=180 | | (4x+8)/12=0 | | 13+11r=2 | | 13=6+p | | -10-6z=10-9z+10 | | -35=-y | | 186=-x+37 | | 2(5k-13)=44 | | 3x-0.45833333333=-1+1/6 | | 8x3=40- | | 2(2+3h)=22 | | 199=66-u | | x-8=-0 | | 4g+5=30-g | | 3x-9=9x+3 | | -.25(x-16)-13.7=2.3 | | 8-5r=-3r-10 |